1998
DOI: 10.1111/j.1439-0426.1998.tb00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic variability of Pasteurella piscicida during in vitro cultivation as a preliminary study for vaccine production

Abstract: During in zritro cultivation of bacteria, the pathogenetic factors may change in amount and quality. Knowledge of this variability is important in vaccine production. The pathogenic variability of Pusteurella piscicida broth culture (BC), extracellular products (ECPs) and whole cells (WC) was investigated in sea bass (Dicentrarchus labras) 2-3 g wet weight, inoculated intraperitoneally. Ten Pasteurellapiscicirla field strains isolated from fish affected by different outbreaks which occurred in Italian fish far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…AIP56 appears as a major protein band in the electrophoretic profiles of exponential culture supernatants of virulent Phdp . It should be noted that the low complexity of the electrophoretic profiles of these supernatants is in contrast to previous studies suggesting the secretion of a highly complex mixture of different proteins by Phdp (Bakopoulos et al ., 1997; Mazzolini et al ., 1998). The larger protein complexity of the culture supernatants observed by those researchers could be explained by the fact that stationary‐phase cultures were used in those studies.…”
Section: Discussionmentioning
confidence: 88%
“…AIP56 appears as a major protein band in the electrophoretic profiles of exponential culture supernatants of virulent Phdp . It should be noted that the low complexity of the electrophoretic profiles of these supernatants is in contrast to previous studies suggesting the secretion of a highly complex mixture of different proteins by Phdp (Bakopoulos et al ., 1997; Mazzolini et al ., 1998). The larger protein complexity of the culture supernatants observed by those researchers could be explained by the fact that stationary‐phase cultures were used in those studies.…”
Section: Discussionmentioning
confidence: 88%
“…Although it has been suggested that Phdp remains in a cultivable form in salt water for only [4][5] days (38,39), it was also suggested that it has the ability to enter a dormant, non-cultivable but infectious state in salt water and sediment (40). With regard to the mechanisms responsible for the pathogenicity of Phdp, it was shown that extracellular products (ECPs) play a fundamental role (41,42) although among their components, only the toxin AIP56 has been identified and characterized so far (43)(44)(45)(46)(47).…”
Section: Introductionmentioning
confidence: 99%
“…(eds) Structural Bioinformatics. Methods in Molecular Biology, vol 2112.Humana, New York, NY, pp [29][30][31][32][33][34][35][36][37][38][39][40][41][42]…”
mentioning
confidence: 99%
“…Although the pathogenesis of the disease is not yet fully understood, its has been reported that the extracellular products (ECPs) of Photobacterium damsela subsp. piscicida ( Phdp ) are major virulence factors contributing to the development of the disease (Mazzolini, Fabris Ceschia, Vismara, Magni, Amadei, Passera, Danielis & Giorgetti 1998) enabling the bacterium to counteract the host's defence mechanisms (Magarinos, Toranzo & Romalde 1996).…”
Section: Introductionmentioning
confidence: 99%